Audit Kinerja Sektor Publik dan Pengawasan Fungsional Terhadap Akuntabilitas Publik Pada Satuan Kerja Perangkat Daerah di Pemerintah Kota Bondowoso - Susbiyani, Arik (Universitas Muhammadiyah Jember, 2016)
This? study? aimed? to? examine:? 1)? The effect of performance audit? to? support? public? accountability? on? Bondowoso ?government 2) The? effect? of? functional ?supervision? to? support? public? accountability? on? Bondowoso ?government. This type of research that is classified as causative research. The population in this study is SKPD Bondowoso. The selection of the sample with total sampling method. The data used in this study in the form of primary data. Data collection techniques with survey techniques by distributing questionnaires to each head and the entire head of the SKPD.The research proves that? performance of audit and functional Supervision significant and positive impact on public accountability. In? this study?? suggested:? 1)? For? a functional? regulatory authorities? in order to? continue to? perform its role? in overseeing the optimal and better? . 2) In the next study? can add variables that affect other Public Accountability such as eksternal control, and supervision of DPRD, Audit performance and Auditor independency .Keywords: performance audit, functional supervision, public accountability